2012
DOI: 10.1111/j.1365-2265.2012.04454.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucocytosis in women with polycystic ovary syndrome (PCOS) is incompletely explained by obesity and insulin resistance

Abstract: Low-grade inflammation occurs in PCOS. Increased hsCRP and cytokines are associated with IR, but increased WCC is observed even when IR is accounted for. The explanation for this and its clinical significance is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 40 publications
5
30
0
2
Order By: Relevance
“…Therefore, we consider that this condition should be further discussed, and more comprehensive studies to enlighten the correlation between MPV, obesity, and PCOS are needed. Increased leucocyte count is an independent risk and prognostic factor in the development of inflammation and atherosclerosis [17], and there are several studies reporting increased leucocyte counts in patients with PCOS [4,7,15,16,35]. In our study, leucocyte counts were similar in patients with PCOS and controls; still, differential count of leucocytes revealed that patients with PCOS had higher neutrophil count and ratio, basophil count and lower lymphocyte count, compared to controls.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Therefore, we consider that this condition should be further discussed, and more comprehensive studies to enlighten the correlation between MPV, obesity, and PCOS are needed. Increased leucocyte count is an independent risk and prognostic factor in the development of inflammation and atherosclerosis [17], and there are several studies reporting increased leucocyte counts in patients with PCOS [4,7,15,16,35]. In our study, leucocyte counts were similar in patients with PCOS and controls; still, differential count of leucocytes revealed that patients with PCOS had higher neutrophil count and ratio, basophil count and lower lymphocyte count, compared to controls.…”
Section: Discussionsupporting
confidence: 47%
“…Additionally, increased leucocyte counts were found to be an additional independent marker and prognostic factor in the development of inflammation and atherosclerosis [4,7,[15][16][17]. In recent years, neutrophil to lymphocyte ratio (NLR) has gained a popularity in the detection of inflammation in different inflammatory diseases such as PCOS, DM, ulcerative colitis, and hypertension, and it has been shown that NLR is correlated with hsCRP levels [4,18,19].…”
Section: Introductionmentioning
confidence: 97%
“…This was a cross‐sectional study in 103 PCOS women and 102 BMI‐matched controls. Some of the data pertaining to the effects of PCOS status on inflammation and functional alterations in lipoprotein particles have previously been reported . The aim was to compare cardiometabolic variables between women with and without PCOS, before and following pair matching for the most promising marker identified in Study 1.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, visceral obesity is well recognized to be associated with low-grade inflammatory states [22]. Previous studies have reported that obese individuals present higher CRP serum concentrations than those with normal weight [23, 24]. …”
Section: Discussionmentioning
confidence: 99%